Moving from the I to we : effective parenting education in groups : a thesis presented in partial fulfilment of the requirements for the Master of Education (Adult Education) at Massey University, New Zealand - Rumble, Claire (Massey University, 2010)
Parenting education has a role to play in helping people positively parent and nurture their children to ensure children experience a warm and loving childhood and reduce the incidence of child abuse and neglect. However, there is no clear picture about the critical elements necessary for parenting education to succeed, specifically those elements which would ensure successful attendance, retention and positive learning outcomes for parents, particularly from ‘hard-to-reach’ families. To help parenting education providers plan effective programmes, this research investigated three programmes regarded as good exemplars of parenting education in New Zealand. There were:  Nurturing the Future, which delivers programmes to low socio-economic families on the West Coast of New Zealand;  the national SPACE programme which is delivered through early childhood sessions where mothers learn alongside their babies;  Te Aroha Noa parent educator model which is delivered within the context of Te Aroha Noa’s community development organization. A bricolage approach using multiple research methods was taken to collect data and stories from the organizers, facilitators and parents and included parent focus groups, semi-structured interviews with organisers and observations of the programmes being delivered. Analysing parents’ stories revealed that positive transformative learning and change occurred in group settings. Allowing parents to reflect and dialogue together in these social settings was more important in achieving learning and positive change than the programmes’ delivery methods and curriculum. The relationship skills of facilitators were critically important. Programmes were enhanced by both child development content (which resulted in deepening parents’ understanding of their children) and opportunities for parents to reflect on their own childhood and how this linked to the way they parented their children (which increased their understanding of themselves). All three programmes had overcome problems commonly reported by other parenting education programmes in the recruitment and retention of parents and in achieving short and long-term benefits. They achieved this by embedding their programmes within their communities, delivering the programmes in groups, weaving through other means of support and enriching them by continually consulting and involving the parents for whom they were intended. This is in contrast to many other parenting education programmes delivered in New Zealand which are universal programmes that have been developed without consulting the communities they are aimed at and which are delivered as short courses without multiple or ongoing methods of parent support.
Keywords: Parenting education; Parent education; Group education; Adult education; New Zealand; Fields of Research::330000 Education::330100 Education Studies::330199 Education studies not elsewhere classified